Political and social activism within the campus community of Wisconsin State University-La Crosse from 1966 to 1970 : local expression of a national movement - Kenneth, Robert C. (My University, 1988)
As events and the people affecting them fade into the past, images often become blurred, ideas and emotions lose currency and depth. It is History's role to somehow capture the essences of a moment and preserve them as faithfully and objectively as possible. So often the happenings of our world are relegated to the "dustbins of history" before each variant facet is explored and recorded. Spans of hundredsor even thousands of years are constricted within terms such as "epoch", "era" or "period", and thus important data become forgotten -- or worse, only cursorily examined. In many vital ways, local history corrects the error, fills the gap and clarifies the ambiguity. This paper is an attempt at local history.
Keywords: Vietnam War, 1961-1975, Social aspects; Vietnam War, 1961-1975, Protests movements; Wisconsin State University (La Crosse)-History; Student movements, Wisconsin